Representações identitárias da mulher no casamento brasileiro do século XIX: o teatro de José de Alencar e Martins Pena - Dal-Bó, Renata Marques de Avellar (2019)
This dissertation intends to analyze how the woman’s identity representations in the Brazilian marriage of the nineteenth century are configured in the plays O que é o casamento? (1861), by José de Alencar (1829-1877), and As casadas solteiras (1845), by Martins Pena (1815-1848). As specific objectives, we intend to evaluate the relation of the historical and fictional contexts presented in the works and the woman’s situation related to love and the economic issue in marriage. José de Alencar and Martins Pena seek, in their plays, represent the Brazilian woman in different kinds of marriage of the nineteenth century, who, although having influence of the European society, mainly French, also looks for her own identity traits. The analysis of the plays will be done through a bibliographical research of qualitative approach, anchored in the perspective of Comparative Literature by Tânia Franco Carvalhal (2006). The methodological procedures of this research was based on the assumptions of the macroanalysis and microanalysis of Massaud Moisés (1984). We observed how each author, through his cultural, moral and ethical particularities, portrays the feminine within his theatrical conception. We highlight the importance of this research as far as the theatrical texts of the nineteenth century make it possible to reflect and criticize the role of women as spouses and mothers in a conservative society in a country that has just been independent, providing a reconstitution of the moral expression of this century and the understanding of the female imaginary in marriage.